Prognostic value of long-term trajectories of depression for incident diabetes mellitus in patients with stable coronary heart disease - Peter, Raphael Simon; Jaensch, Andrea; Mons, Ute; Schöttker, Ben; Schmucker, Roman; Koenig, Wolfgang; Brenner, Hermann; Rothenbacher, Dietrich (Cardiovascular diabetology, 2021)
Diabetes mellitus (DM) and depression are bidirectionally interrelated. We recently identified long-term trajectories of depression symptom severity in individuals with coronary heart disease (CHD), which were associated with the risk for subsequent cardiovascular events (CVE). We now investigated the prognostic value of these trajectories of symptoms of depression with the risk of incident DM in patients with stable coronary heart disease.